Analisis Pengelolaan Keuangan Pendidikan Dalam Meningkatkan Akuntabilitas Dan Transparansi Pada Tk Panti Rini - Sulastri, Hermina; Rengga, Andreas; Jaeng, Wihelmina Maryetha Yulia (Universitas Nusa Nipa Maumere, 2026)
This study examines the management of educational finances at TK Panti Rini with a focus on accountability and transparency. A descriptive qualitative approach was employed, utilizing observation, interviews, and documentation techniques. The results show that the financial management system at TK Panti Rini has implemented proportional mechanisms of planning, control, accountability, and transparency. Although the financial reporting has not fully adopted non-profit accounting standards such as ISAK 35, periodic supervision by the Foundation enhances monitoring and evaluation of fund management effectiveness. These findings indicate that the institution has applied accountability principles consistent with good governance practices.